The importance of fundamental motor skills in identifying differences in performance levels of U10 soccer players - Jukic, I.; Prnjak, K.; Zoellner, A.; Tufano, J. J.; Sekulic, D.; Salaj, S. (Sports, 2019)
Abstract This study examined the differences in fundamental motor skills (FMSs) and specific conditioning capacities (SCCs) between a coach`s classification of first team (FT) and second team (ST) U10 soccer players and examined the most important qualities based on how the coach differentiates them. The FT (n = 12; Mage = 9.72 ± 0.41) and ST (n = 11; Mage = 9.57 ± 0.41) soccer players were assessed using the Test of Gross Motor Development-2, standing long jump, sit and reach, diverse sprints, and the 20 m multistage fitness test (MSFT). The coach`s subjective evaluation of players was obtained using a questionnaire. No significant differences existed between the FT and ST in any variables (p > 0.05). However, large and moderate effect sizes were present in favour of the FT group in locomotor skills (d = 0.82 (0.08, 1.51)), gross motor quotient (d = 0.73 (0.00, 1.41)), height (d = 0.61 (-0.12, 1.29)), MSFT (d = 0.58 (-0.14, 1.25)), and maximum oxygen uptake (VO2max) (d = 0.55 (-0.17, 1.22)). Furthermore, the coach perceived the FT group as having greater technical and tactical qualities relative to ST players. This suggests that it might be more relevant for players of this age to develop good FMS connected to technical skills, before focusing on SCC. Therefore, it might be beneficial for soccer coaches to emphasize the development of FMSs due to their potential to identify talented young soccer players and because they underpin the technical soccer skills that are required for future soccer success.